Sejarah Politik Islam: Pandangan Islam terhadap Politik dan Periode Awal Perpolitikan Islam - Muhammad Mukhlis (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
The success of Islam in world civilization is inseparable from the geopolitical aspects carried out by the Prophet Muhammad. even politics is very effective as a means of da'wah media and welfare media for the Ummah. So the making of this paper aims to examine the understanding of Islamic politics, politics in the views of Qur'anic figures and perspectives and the history of Islamic politics during the time of the Prophet Muhammad (peace be upon him) in Medina. The early period of the politics of the Prophet Muhammad (saw) in Medina began with his appointment as head of state, then, some political strategies carried out by the Prophet Muhammad (saw) were by building mosques, fraternizing among fellow Muslims, forming the charter of Medina, defending the territory and honor of Islam and diplomacy.